Pengaruh Literasi Keuangan Syariah dan Sikap Keuangan Syariah Terhadap Perilaku Manajemen Keuangan - Iqbal Asrian Amin; Rahmat Mulyana; Zulkarnain Muhammad Ali (Economic Reviews Journal, 2024)
The purpose of this study was to determine the effect of Islamic financial literacy and Islamic financial attitudes on financial management behavior. This study determines the factors that influence Islamic financial literacy, namely basic Islamic financial knowledge, knowledge of Islamic debt concepts, Islamic investment knowledge, knowledge of risk management and protection of Islamic assets and factors that influence Islamic financial attitudes are distrust, retention time, power-prestige, quality, and anxiety. A total of 200 questionnaires were distributed to all Jabodetabek people randomly with the criteria of being Muslim, having an identity in Jabodetabek, and having income. The analytical method used is Path Analysis or path analysis. The results of the study indicate that Islamic financial literacy and Islamic financial attitudes owned by a person will have a significant positive effect on one's locus of control and financial management behavior directly. However, the locus of control did not succeed in mediating the variables of Islamic financial literacy and Islamic financial attitudes on financial management behavior. So it means that if someone has Islamic financial literacy and good Islamic financial attitude, it will affect the locus of control and good financial management behavior.